Freeze-thaw-induced greenhouse gas emissions from a Mollisol agroecosystem: Microbial and edaphic regulation under long-term agricultural management - Dan-Dan Wang; Shan-Shan Dai; Peng He; Zhi-Ming Zhang; Jian-Ying Zhou; Ming-Hui Liu; Shi-Xiu Zhang; Lu-Jun Li (Soil and Tillage Research, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

The critical x[I/L]xbS motif in adaptor proteins, MAVS, MITA, and TRIF contributes to type I IFN production and antiviral immune response in fish - Xue Yun Peng; Jing Hou; Bo Li; Chuan Yun Zhang; Lin Huang; Lan Hao Liu; Nan Li; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

A triazine-hydrazine-based covalent organic framework for deep removal of trace benzo[a]pyrene from petroleum products - Shigang Guo; Shan Jiang; Xin Li; Wen Sun; Jianjun Du; Jiangli Fan; Danhong Zhou; Xiwen Zhang; Xiaojun Peng (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Freeze-thaw-induced destabilization of organic matter in Mollisols after decadal mineral fertilization - Dan-Dan Wang; Zhiming Zhang; Peng He; Shan-Shan Dai; Minghui Liu; Yu Luo; Tida Ge; Ekaterina Filimonenko; Yakov Kuzyakov; William R. Horwath; Lu-Jun Li (Soil Biology and Biochemistry, 2026)

Coupled mineral and microbial carbon pumps govern soil organic carbon accumulation in croplands at a large spatial scale - Shan-Shan Dai; Peng He; Zhiming Zhang; Dan-Dan Wang; Xuexian Zhang; Bingxue Zhu; Kaishan Song; Junjie Liu; Xia Zhu-Barker; Lu-Jun Li (Soil Biology and Biochemistry, 2026)

Perioperative administration of fucoidan induced changes in immune cell composition and resulted in no beneficiary outcomes in the acute phase of postoperative neurocognitive recovery - Cundong Liu; Linpeng Li; Wenyi Wang; Yuan Zhou; Xiaosheng Liang; Chao Song; Bo Peng; Shan Xiao; Shufang Li; Yi Zou (Food Research International, 2026)

Dual role of cold plasma in suppressing the growth, remodeling cellular ultrastructure and stimulating metabolic response of Kazachstania exigua from transcriptomic insight - Binyao Wang; Qing Du; Liangpeng Yuan; Longhua Pan; Yi Tang; Menglu Yang; Wenjian Wang; Dengshui Peng; Huajia Li; Shan Zeng; Lihong Ge; Jianping Yang; et al. (Food Research International, 2026)

Multiscale protection of anthocyanin via zein/cinnamaldehyde/sodium alginate core-shell nanoparticles enable UV-stabilized colorimetric label for monitoring shrimp and fish freshness - Zhihang Xu; Hong He; Jian Du; Peng Shan; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Yanna Lv; Haisong Wang (Food Chemistry, 2026)

Development of ammonia-sensitive carboxymethyl cellulose/pectin colorimetric films with sodium lignosulfonate-regulated ZIF-67 for pork freshness monitoring - Zhihang Xu; Jian Du; Peng Shan; Yali Zhao; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Yanna Lv; Haisong Wang (Food Bioscience, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Interactive migration of heavy metals between dust and soil demonstrated by the coupling coordination analysis - Xi Wang; Shan Li; Peng Liu; Yiwen Xu; Xuanning Cao; Zhongming Wu; Zhenhua Miao; Junkang Guo (Environmental Monitoring and Assessment, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

Biotransformation of Cimetidine by Chlamydomonas sp. SI-16: CYP450-Driven Detoxification and Immobilized Photobioreactor Validation - Kang Li; Jun Liu; Yongtao Cheng; Chenxi Zhou; Kang Shan; Chuanyue Peng; Wenjing Yan; Ying Liu; An Xu; Min Zuo (Journal of Hazardous Materials, 2026)

Perfluorooctanoic acid disrupts lysine metabolism and autophagy to promote white spot syndrome virus infection in shrimp - Li-Peng Shan; Mao-Mao Wang; Lei Liu; Jiong Chen (Journal of Hazardous Materials, 2026)

Peak prediction and emission reduction pathways of building operational carbon emissions in Eastern China - Shanbi Peng; Wen Li; Enbin Liu; Xianbin Zheng; Xinyu Shan; Jiayi Tan (Journal of Cleaner Production, 2026)

Functional probiotic Ligilactobacillus agilis Z22 enhances gut–lung immune defense in chickens through TLR2/IL-10–JAK1/STAT3 signaling - Qiao Guo; Yingjie Wang; Jiahui Wu; Zhenghao Che; Shan Lv; Wenqing Zhao; Shiying Li; Jin Liu; Xiuli Peng (Food Bioscience, 2026)

Ion-shielded emulsions enabling salt stability and synergistic pH-responsive release for high-salinity food preservation - Peng Shan; Jian Du; Zhihang Xu; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Jijuan Cao; Dong Lv; Haisong Wang (Food Packaging and Shelf Life, 2026)

Mango peel pectin as a high-ester emulsifier for carotenoid delivery: Structural characterization and application in low-fat ice cream - Teng-Gen Hu; Huan Zhang; Lu Li; Yu-Qing Hu; Jing Wen; Bo Zou; Jian Peng; Li-Na Cheng; Ji-Jun Wu; Geng-Sheng Xiao; Yu-Juan Xu; Yuan-Shan Yu (Carbohydrate Polymers, 2026)

Suitable particle-size biochar enhances resilience of potato production and soil environmental to irregular precipitation in semiarid region - Zhaoyang Li; Nan Shi; Zhimin Yang; Yubo Cao; Shimeng Fan; Musawer Abbas; Weixing Shan; Ansabayeva Assiya; Zhikuan Jia; Enke Liu; Kadambot H.M. Siddique; Ruixia Ding; et al. (Bioresource Technology, 2026)

Photocatalytic degradation of diclofenac using iron-doped hydrothermal carbonation carbon coupled with peroxydisulfate: Insights into reactive species contributions and degradation pathways via density functional theory - Chao Zhang; Yutong Zhang; Yueyao Cheng; Meifang Li; Yuanhao Peng; Hao Xu; Siwei Kang; Yuan Ouyang; Zhihang Yuan; Shan Xie; Chuansheng Chen (Bioresource Technology, 2026)

Study on oxidative stress and nitric oxide response mechanisms in Gymnodinium sp. under polystyrene microplastic stress - Zhen Ren; Zheng–Xin Hu; Xue Deng; Pei–Feng Li; Chun–Ying Liu; Shan–Shan Duan; Xiang–Feng Kong; Gui–Peng Yang (Journal of Applied Phycology, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Intracranial EEG reveals working memory-related dynamics and connectivity in human white matter - Shen Zhang; Peng-Hu Wei; Longzhou Xu; Chao Zhang; Na Ao; Haoshu Xu; Yanfeng Yang; Lirou Tan; Zhilin Li; Yali Huang; Jin Li; Jing Liu; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Enhancement of anammox coupled arsenate reduction by coexisting iron-bearing minerals - Wentao Wang; Weiyi Xiong; Qing Jiang; Long-jun Ding; Ping Wang; Jiang-Shan Li; Hui Yin; Peng Cai (Journal of Hazardous Materials, 2026)

Indium enrichment in VMS deposits: insights from sphalerite geochemistry and thermodynamic modeling of the Tiemurt Pb-Zn-Cu deposit, NW China - Min Luo; Peng-Peng Yu; Yi Zheng; Jie-Jun Lei; Xi Chen; Yi-Han Wu; Hong-Xiang Shan; Quan-Jie Li; Zhuo-Xiong Shi (Journal of Geochemical Exploration, 2026)

Accelerated degradation of antiviral ribavirin by microalgae fuel cell (MFC), electricity generation and key metabolic process - Junhao Wang; Xinrui Qin; Jiajia Ge; Yongtao Cheng; Kang Li; Jun Liu; Kang Shan; Chuanyue Peng; Wenjing Yan; Juan Wang; Min Zuo; Ying Liu (Journal of Environmental Chemical Engineering, 2026)

Beyond pathogens: Emerging contaminant risks following the potomac sewer spill in the United States - Xiaopei Li; Qing Feng; Zhenheng Long; Kunyu Guo; Bin Liu; Peng Gao; Shan Niu; Gang Yu (Journal of Environmental Sciences, 2026)

Research advances in machine learning-aided accurate prediction of the impact of exogenous substances on anaerobic digestion - Chuqiao Wang; Zijing Wang; Runjie Deng; Shan Huang; Yuying Hu; Dingchang Li; Xiaoming Peng; Xizi Long; Jiajie Zhang (Bioresource Technology, 2026)

PM2.5 and ozone in the yangtze river economic belt, 2013–2023: Dynamics and drivers, with scenario-based PM2.5 projections and health implications to 2050 - Yiwei Chen; Haixing Zhao; Sen Li; Guangmao Zhang; Zhouyi Du; Ting Huang; Shan Huang; Xiang Tu; Zugen Liu; Honggen Peng (Atmospheric Pollution Research, 2026)

A promising strategy to battle Enterocytozoon hepatopenaei infection in shrimp: dual action of paeonol on spore inhibition and immune activation - Li-Peng Shan; Mao-Mao Wang; Si-En Wang; Yang Hu; Lei Liu; Jiong Chen (Aquaculture, 2026)

A single-cell transcriptomic atlas of the spotted scat testis reveals two Sertoli cell subclusters with differential dmrt1Y expression - Yu Li; Mou-Yan Jiang; Shan-Ni Cao; You-Xing Peng; Yuan-Qing Huang; Hong-Juan Shi; Hua-Pu Chen; Tian-Li Wu; Dong-Neng Jiang (Aquaculture, 2026)

p-Block metal boosted oxygen electrocatalysis of Fe–N–C for alkaline seawater electrolyte-based zinc-air batteries - Yuxin Zhang; Yurong Liu; Xue Zhang; Meizhen Chen; Min Chen; Jing Li; Zhitong Wang; Yonghao Xiao; Xiaodong Shi; Zhenye Kang; Zhuoliang Jiang; Lutong Shan; et al. (Science Bulletin, 2026)

Type I IFNs, IFNc, IFNd1, IFNd2, IFNh, and type II IFNs, IFN-γ and IFN-γrel, and their possible receptors with the identification of two variants of IFNc and IFNh in turbot (Scophthalmus maximus) - Bo Li; Meng Xin Yan; Yu Hang Deng; Xiao Qian Jiao; Shan Nan Chen; Xu Jia Zhang; Jia Le Chen; Xue Yun Peng; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Assessing the unequal distribution between social benefits and costs across countries along global supply chains - Danyang Zhang; Hui Wang; Christina Prell; Jin Yan; Yanxian Li; Peng Zhou; Yuli Shan; Klaus Hubacek (Ecological Economics, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Research on microseismic source localization method combining supervised machine learning and 3-dimensional ray tracing method - Qi Ma; Peng Chen; Yunpeng Zhang; Tiancheng Shan; Kailong Qian; Jiahui Du; Xinke Chang; Xue Li; Shanxi Wu (Arabian Journal of Geosciences, 2026)

DHX36 initiates the transcription of type I IFNs through TRIF signaling in fish - Xue Yun Peng; Shan Nan Chen; Chuan Yun Zhang; Jia Le Chen; Bo Li; Yu Hang Deng; Xiang Yang Wu; Nan Li; Lan Hao Liu; P. Nie (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The dual origin of granites from fluid-absent and fluid-fluxed melting of the juvenile lower crust: New constraints from Mo isotopes and phase equilibrium modeling - You-Shan Xia; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Yao Zhou; Zhen-Xin Li; Gang Wen; Lei Qin (Geochimica et Cosmochimica Acta, 2026)

Mechanism of Prestress Loss in Anchor Cables Embedded in Two-Region Composite Rock Masses: Development and Analysis of a Coupled Model - Renliang Shan; Haobo Bai; Dong Liu; Hailong Wang; Mingyue Nie; Yongzhen Li; Peng Sun; Haotian Wu; Shengchao Xiao (Rock Mechanics and Rock Engineering, 2026)

Decoding the role of CXC chemokines in pulmonary metastasis of colorectal cancer using integrative computational approaches - Peng Meng; Fengjuan Zhang; Shan Li; Xiaodong Fan; Xiaoping Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Deciphering programmed cell death for gastric cancer prognosis: AKR1B1 as a key player - Shan-peng Liu; Xiaomin Li; Qin Liu; Shun Xie (Journal of Applied Genetics, 2026)

Performance assessment of anchor cable with high-strength C-shaped tube under double shearing - Ye Chen; Renliang Shan; Yichao Peng; Lichong Li; Zonghui He (Tunnelling and Underground Space Technology, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Light-at-night exposure drives myopia via melanopsin signalling - Jiaxin Li; Congying Li; Meijun Wang; Jianjun Meng; Jiajia Dang; Ying Huang; Di Shi; Xinyu Li; Shan Cai; Tianli Peng; Yunfei Liu; Yuting Kang; et al. (Science China Life Sciences, 2026)

Deep fertilization effects on potato production and GHG emissions depend on soil C:N:P-enzyme interactions: Evidence from a 4-year study - Zhaoyang Li; Nan Shi; Yixuan Yuan; Haiyang Chang; Yuling Meng; Weixing Shan; Moskvicheva Elena; Ansabayeva Assiya; Zhikuan Jia; Xiaolong Ren; Kadambot H.M. Siddique; Ruixia Ding; et al. (European Journal of Agronomy, 2026)

Chirality-driven cerium-doped ZnO nanoparticles with enhanced antibacterial and anti-inflammatory activities for wound healing - Longhua Wei; Xin Wang; Si Li; Hongmiao Gao; Shan Sun; Hengwei Lin; Chuanlai Xu; Peng Wang (Chemical Engineering Journal, 2026)

TNFR-CD3–engineered regulatory T cells attenuate neuroinflammation and neuropathic pain - Pei Li; Ying Yan; Shan Wu; Peng He; Wei Wang (Immunologic Research, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Dual role of polyphenols in walnut protein extraction and functionality: Implications for processing and utilization - Yu Peng; Ziming Shan; Wanqing Jia; Jingming Li; Lei Zhang; Congfang Li; Mo Li; Xin Wen; Yuanying Ni (Food Hydrocolloids, 2026)

Adjusting fertilization depth for sustainable potato production in arid and semi-arid regions - Zhaoyang Li; Yukang Wang; Nan Shi; Yixuan Yuan; Lianjun Wei; Weixing Shan; Medelbek Meruyert; Ansabayeva Assiya; Zhikuan Jia; Kadambot H.M. Siddique; Ruixia Ding; Peng Wu; et al. (Field Crops Research, 2026)

Chiral CD@Ag2O nanoparticle-mediated highly efficient antibacterial activity based on synergistic multi-pathway interactions - Xiang Li; Qi Ding; Si Li; Junru Li; Heng Zhang; Shan Sun; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Bio-template synthesis of graphitized carbon-decorated Fe2O3 hierarchical tubes for high-response and low-temperature H2S detection - Ming-Yan Cao; Hui-Nan Lei; Hui-Ye Jiang; Ya-Nan Li; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2026)

Genome-Wide Identification and Expression Analysis of the TCP Gene Family in Quinoa (Chenopodium quinoa Willd.) - Yutao Bai; Heng Zhang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Rongbo Li; et al. (Journal of Plant Growth Regulation, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

Effects of high-pH saline-alkaline water on tissue structure, osmoregulation, antioxidant capacity, and metabolic activity in mud crab Scylla paramamosain Estampador, 1950 - Yuntao Li; Cunhong Chen; Zihui Li; Jingli Yang; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; et al. (Aquaculture, 2026)

Durable superhydrophilic zwitterionic polyurethane coating for oil–water separation - Jinlong Wu; Peng Wang; Qianqian Li; Yukun Tian; Xinyu Yang; Shan Liang (Journal of Environmental Chemical Engineering, 2026)

Trace element geochemistry of magnetite and hematite from the Jinchang porphyry Au-Cu deposit, northeast China: Implications for fluid evolution and cobalt enrichment - Peng-Fei Shan; Ming-Jian Cao; Noreen J. Evans; Le Wang; Yi Li; Yu-Suo Zhao; Ke-Zhang Qin (Journal of Asian Earth Sciences, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

Enhancing free hydroxyl radical generation via noble metal-modified TiO₂ for efficient benzisothiazolinone degradation with reduced H₂O₂ consumption - Meng Xu; Xiao-qing Dong; Li-fang Chen; Ping Yu; Xin-yu Li; Shan-shan Lv; Ya-wen Qi; Wei Zhang; Peng Jiang; Xiao-long Zhou (Journal of Water Process Engineering, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Corrigendum to “Mortality risk of short-term air pollution exposure in urban and rural Chinese populations: A nationwide time-stratified case-crossover study, 2008–2020” [Int. J. Hyg Environ. Health 266 (2025) 114564] - Yunning Liu; Hongbing Xu; Xuyang Shan; Xinpeng Guan; Lijun Wang; Xinghou He; Jiangmei Liu; Jinling You; Rongshan Wu; Jianbin Wu; Bin Zhang; Jinlei Qi; et al. (International Journal of Hygiene and Environmental Health, 2026)

Molecular insight into the formation mechanism of CO2 hydrate in a confined space of surface oxidized porous media system - Xuemin Zhang; Tao Shan; Yetao Zhang; Hongbin Song; Jinping Li; Qingbai Wu; Peng Zhang (Fuel, 2026)

“Two-pronged” active packaging films enable biogenic amine scavenging and controlled Ferulic acid release for pork preservation - Hong Wang; Peng Shan; Jian Du; Chao Li; Yehan Tao; Jinwen Hu; Jie Lu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang (Chemical Engineering Journal, 2026)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

A starch-based composite film with dual-modality essential oil controlled-release for perishable fruit preservation - Shikai Zhang; Haonan Guo; Houshen Li; Xinbei Qiao; Peng Wu; Yijing Li; Shiyun Ai; Yang Shan; Shenghua Ding (Food Packaging and Shelf Life, 2025)

Receptor affinity-selective differential dynamics of membrane fusion initiation govern deltacoronavirus cross-species transmission - Da An; Qi Peng; Yong-Hao Ma; Wenguang Hong; Yi Pei; Shiyu Liu; Yan Li; Jizong Li; Yanke Shan; Yulong Yin; Bin Li; Fei Liu (Science China Life Sciences, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Identification of homeobox gene family in Chenopodium quinoa and expression patterns in response to flooding stress during the filling stage - Guofei Jiang; Li Li; Yutao Bai; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

The evolution of organic matter sources and sedimentary environments in lakes during the Eocene Climatic Optimum - Chuan Xu; Guangrong Peng; Pei Liu; Ye He; Peimeng Jia; Xuanlong Shan; Guoli Hao; Mengrong Shen; Kang Li (Marine and Petroleum Geology, 2025)

Establishing a robust area-to-volume scaling for Qinghai-Tibetan Plateau Retrogressive Thaw Slumps: A key tool for quantifying mass wasting and carbon release induced by permafrost degradation - Jiapei Ma; Genxu Wang; Chunlin Song; Dexin Gao; Jinlong Li; Peng Huang; Linmao Guo; Kai Li; Shan Lin; Shouqin Sun (Global and Planetary Change, 2025)

Topography-engineered cobalt-based microparticles for biofilm-eradicating medical device disinfection: Overcoming antibacterial resistance through mechano-bactericidal action - Ke Cheng; Shan Sun; Wenhao Zheng; Heng Zhang; Henggang Wang; Shang Gao; Si Li; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Spontaneously oriented receding on superhydrophobic bundles for high-efficiency enrichment of airborne microdroplets - Shan Peng; Peibin Liang; Mingzhan Wang; Zhao Li; Huanhuan Dong; Xueji Zhang; Hubao A; Shuang Zheng; Yuanyuan Zhao (Chemical Engineering Journal, 2025)

Eco-friendly taro stem-sourced cellulose/polypyrrole hybrid aerogel: An efficient capture strategy for microplastics removal - Wei-peng Qiu; Hai-ze Su; Hao Su; Shao-hua Luo; Li-shan Lai; Jia-le Zhu; Zhen-lin Xu; Hong Wang; Peng Wen (Chemical Engineering Journal, 2025)

m6A deficiency impairs uterine spiral artery remodeling to induce preeclampsia-like symptoms via FGF2 - Sun Liu; Wenqian Chen; Jiaqi Chen; Tianqi Liu; Mingqiang Deng; Linjian Xia; Zengguang Li; Junfang Shi; Yuan Li; You Peng; Qihuan Ren; Ziteng Miao; et al. (Science China Life Sciences, 2025)

ATF-4 deficiency increases ER stress and induces osteoarthritis formation in mice - Peng-Yu Xie; Shan-Shan Li; Xu Liang; Hang Ma; Ying-Chao Yang; Tian-Fang Li (Molecular and Cellular Biochemistry, 2025)

Genome-Wide Identification of the DVR Gene Family and Expression Analysis of GDF8 Genes in Qihe Gibel Carp - Jinyan Shan; Yuling Liu; Kaiqi Lian; Xianghui Xiao; Jun Ma; Ren Ren; Xiaolong Li; Guoqiang Wei; Youyi Kuang; Renhai Peng (Fishes, 2025)
(1) Background: The BMP/GDF (Bone Morphogenetic Protein/Growth Differentiation Factor) subfamily (Decapentaplegic-Vg1-related, DVR) within the transforming growth factor beta (TGF-β) superfamily plays critical roles in governing biological developmental processes and physiological functions. (2) Methods: In this study, we systematically investigated the DVR gene family in hexaploid Qihe gibel carp (Carassius gibelio var. Qihe) through comprehensive genomic identification, phylogenetic analysis, chromosome mapping, and cis-regulatory element prediction. The experimental design for gene expression analysis involved collecting samples from multiple tissues (brain, muscle, liver, kidney, etc.) and different developmental stages (20, 45, and 60 days post hatching, dph) to examine the expression patterns of four GDF8 genes using quantitative real-time PCR (qRT-PCR). (3) Results: We identified 50 DVR members in Qihe gibel carp. Phylogenetic analysis classified the 50 DVR family members into 20 distinct protein types, with 29 BMPs (Bone Morphogenetic Proteins) and 21 GDFs (Growth Differentiation Factors) identified. All 50 DVR proteins of Qihe gibel carp have similar TGF-β domains except for four BMP1 proteins. Chromosomal localization revealed widespread distribution of DVR members across 36 chromosomes, a pattern potentially linked to the hexaploid genome of Qihe gibel carp. Genes within the same subgroup exhibited conserved intron–exon architectures and similar intron numbers; syntenic conservation within subgroups may reflect functional constraints after polyploidization, implying evolutionary pressure to maintain functional domains. Through spatiotemporal expression profiling, we uncovered functional divergence among four GDF8 (myostatin) paralogs: GDF8-1 and GDF8-2 were predominantly expressed in brain and muscle tissues (dorsal and caudal), while GDF8-3 and GDF8-4 showed hepatic, cerebral, and renal specificity. Intriguingly, all paralogs exhibited a gradual upregulation during late development (20–60 days post hatching, dph), with peak expression staggered between 45 dph (GDF8-1/2) and 60 dph (GDF8-3/4). (4) Conclusions: These findings suggest that GDF8 plays a critical regulatory role in the growth and development of Qihe gibel carp. Collectively, these results provide a foundation for further investigations into the functional roles of the DVR gene family during the ontogenetic development of this species.

Strong coupling between the carbon and nitrogen cycles, environmental change, and organic carbon enrichment during the early–middle Eocene - Chuan Xu; Guangrong Peng; Pei Liu; Ye He; Peimeng Jia; Xuanlong Shan; Guoli Hao; Mengrong Shen; Kang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Non-destructive, fast and intelligent identification of coal and gangue via spatial-spectral fusion of hyperspectral images - Zhenhao Xu; Shan Li; Peng Lin; Qianji Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Development of gelatin-based antibacterial composite films incorporating dialdehyde starch and AgNPs@MXene for active food packaging - Junxian Yang; Peng Shan; Fangfei Sun; Liping Sun; Kun Wang; Yongliang Zhuang; Hui Li; Lincai Peng (Food Chemistry, 2025)

Sulfur-induced electron migration in thin-layered Bi2MoO6 triggers 1O2-dominated pathway for selective NO photoconversion - Hongjing Liu; Shan Ren; Xiaodi Li; Qingqing Zhou; Yao Yang; Peng Chen; Shouning Chai; Chi He; Bofeng Bai; Fan Dong (Chemical Engineering Journal, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Undescribed isoprenoids obtained from Dictamnus dasycarpus Turcz and their cytotoxic activities - Sun Ye; Si-Yi Wang; Yang Xu; Jia-Tong Wu; Juan Pan; Zhi-Chao Hao; Wei Guan; Zhen-Peng Xu; Yuan-Yuan Zhou; Shao-Wa Lv; Qing-Shan Chen; Li-Li Zhang; et al. (Natural Product Research, 2025)

Genome-wide identification and expression analysis of C2H2 zinc finger protein transcription factor in quinoa - Xuqin Wang; Xingmei Zong; Guofei Jiang; Lingyuan Zhang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

VUV photoelectron ionization source for molecular beam mass spectrometer and its application for SF6 discharge product detection - Peng Liu; Chenxin Wu; Shan Deng; Yuanyuan Xie; Lei Hua; Haiyang Li; Shengrui Yu; Ping Chen (Analytica Chimica Acta, 2025)

Discovery of undescribed schinortriterpenoids from Schisandra chinensis by molecular networking and their neuroprotective effects - Peng Jiang; Yu-Meng Luo; Xin-Yuan Li; Shu-Jun Zhang; Wei Guan; Anam-Naseem; Yu-Hang Fan; Qing-Shan Chen; Li-Li Zhang; Hong-Yan Yao; Xiao-Xue He; Hai-Xue Kuang; et al. (Phytochemistry, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Mechanism of O2-enhanced NO removal driven by Fe(II)EDTA synergistic Z-Scheme WO3/g-C3N4 heterojunction - Liwei Ma; Heting Li; Bo Peng; Shaonan Shan; Guoqiang Li; Guojie Zhang (Journal of Cleaner Production, 2025)

Controls of provenance changes and chemical weathering on organic matter accumulation in lacustrine basins: A case study of the early–middle Eocene Wenchang Formation in the eastern Yangjiang Sag, Pearl River Mouth Basin, northern South China Sea - Chuan Xu; Guangrong Peng; Pei Liu; Xuanlong Shan; Guoli Hao; Peimeng Jia; Kang Li (Journal of Asian Earth Sciences, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Safety evaluation of Bifidobacterium pseudocatenulatum E−0810 and its synbiotic formulation with xylooligosaccharides in alleviating LPS-induced inflammation in intestinal epithelial cells - Zhenyu Yang; Xinyu Wang; Shan Wu; Yu Xin; Peng Du; Guofang Zhang; Chun Li; Libo Liu (Food Bioscience, 2025)

Multi-mechanism cross-linking driven chain spacing shortening to construct polysaccharide-based active packaging films with high water resistance and intelligent controlled release - Zhihang Xu; Jian Du; Peng Shan; Yilin Wang; Leping Li; Yehan Tao; Jinwen Hu; Chenglong Fu; Yanna Lv; Zhenglei Jia; Xunyu Song; Haisong Wang (Chemical Engineering Journal, 2025)

Selective enrichment of potential pathogens and antibiotic resistance genes derived from farmland residual microplastic films - Gaoxiang Huang; Hao Wang; Zhenling Li; Xiaokang He; Guangchun Shan; Peng Wang; Mingjun Ding; Chenghong Feng (Applied Soil Ecology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Flavonoids and butanolides from the bark of Machilus robusta and their bioactivities - Rui-Qi Liu; Shan-Shan Ling; Xian-Da Hu; Bing Peng; Yan-Ru Li (Phytochemistry Letters, 2025)

Effect of organic carbon enrichment on halogenated organic pollutants in wetland sediments of the Yellow River Estuary and Jiaozhou Bay, China - Zi-Cen Zuo; Shan-Shan Liu; Jie Ni; Ya-Li Cao; Zhen He; Gui-Peng Yang (Environmental Research, 2025)

Tetrahydropalmatine exhibits anti-parasitic activity: A novel control strategy against Enterocytozoon hepatopenaei infection in shrimp - Li-Peng Shan; Mao-Mao Wang; Yang Hu; Lei Liu; Bin Zhu; Jiong Chen (Aquaculture, 2025)

In-situ passivation of perovskite films by parallel surface adsorption of dual-active-site ammonium cations for high-performance inverted perovskite solar cells - Guanlin Li; Zebing Gao; Guogen Huang; Jinxing He; Kangbo Sun; Xinting Wang; Haohua Wu; Chuanlin Gao; Xianghui Zeng; Xianfang Zhou; Hanlin Hu; Yunfei Hu; et al. (Chemical Engineering Journal, 2025)

Cytotoxicity phenylpropanoid amides from the seed of Cannabis sativa L - Ao-Fei Wang; Juan Pan; Xiang Liu; Xin-yuan Li; Peng Jiang; Meng-Meng Li; Wei Guan; Qing-Shan Chen; Li-li Zhang; Hai-Xue Kuang; Yan Liu; Bing-You Yang (Natural Product Research, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Heat-triggered CRISPR/Cas12a microspheres for one-pot assays - Siying Xie; Shan Shao; Jin Wang; Jing Qu; Ying Cai; Xingyan Lai; Nan Min; Lidan Zhang; Yan Shi; Tingdong Li; Xiaomin Zhang; Bo Peng; et al. (Science Bulletin, 2025)

Waste utilization to construct highly stable and rapid photothermal superwetting textiles for efficient separation of viscous oil/water mixture - Huanhuan Dong; Junxiang Guo; Zhao Li; Xiaoyu Ji; Shan Peng (Journal of Environmental Chemical Engineering, 2025)

Differential magmatism and tectonic evolution during the rift stage within the Baiyun Sag of the Pearl River Mouth Basin in the northern South China Sea - Bo Yan; Xuan-Long Shan; Zhe Wei; Guo-Li Hao; Peng-Lin Zhang; Ling Ma; Zhi-Hao Wang; Pu-Jun Wang; N.G. Boriskina (Gondwana Research, 2025)

Eco-friendly chitosan-based composite film with anti-dissolution capacity as active packaging for fruit preservation - Jingyi Zhao; Huijie Yang; Chao Li; Zhihang Xu; Peng Shan; Chenglong Fu; Yehan Tao; Jinwen Hu; Haisong Wang; Jian Du (Food Hydrocolloids, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Greenness, nighttime light, and couple fecundability: A national cohort study between 2014 and 2020 - Mengyao Li; Xinghou He; Bin Zhang; Hongbing Xu; Jianbin Wu; Xuyang Shan; Ya Zhang; Huiying Xu; Hongguang Zhang; Yuan He; Yan Fang; Zuoqi Peng; et al. (Environmental Research, 2025)

Membrane-associated NAC transcription factor MaNAC169 is a positive regulator during banana fruit ripening - Fan Liu; Xueli Sun; Jia He; Jingjing Shan; Ou Sheng; Tongxin Dou; Yaoyao Li; Weidi He; Qiaosong Yang; Chunhua Hu; Huijun Gao; Xinxiang Peng; et al. (Postharvest Biology and Technology, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Present-day geothermal regime of the Junggar Basin, northwest China: Implication for hydrocarbon distribution and geothermal resources - Chenxing Li; Jian Chang; Nansheng Qiu; Huajun Guo; Xiang Shan; Bo Peng; Jiabo Xu; Ze Zhang (Journal of Asian Earth Sciences, 2025)

Mortality risk of short-term air pollution exposure in urban and rural Chinese populations: A nationwide time-stratified case-crossover study, 2008–2020 - Yunning Liu; Hongbing Xu; Xuyang Shan; Xinpeng Guan; Lijun Wang; Xinghou He; Jiangmei Liu; Jinling You; Rongshan Wu; Jianbin Wu; Bin Zhang; Jinlei Qi; et al. (International Journal of Hygiene and Environmental Health, 2025)

Temperature-tuned dual-selective NO2/diisopropylamine sensor based on (NH4)0.33WO3 doped γ-WO3 nanosheets-assembled hollow microspheres via simple pyrolysis of commercial ammonium metatungstate - Guo-Li Chen; Hui-Ye Jiang; Yan Jiang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2025)

Experimental study on the adsorption mechanism and desorption of guar gum with different structures on quartz surfaces - Peng Shi; Shibin Wang; Yipeng Li; Xuhua Xia; Li Bao; Shan Xu (Carbohydrate Polymers, 2025)

Dynamic effects of Aeromonas sobria infection on intestinal morphology, microbiota and goblet cells of rainbow trout (Oncorhynchus mykiss) - Li-Ping Liu; Peng-Tian Kang; Feng-Yuan Ding; Dong-Hong Shao; Bao-Shan Wang; Juan Yang; Wen-Hui Gao; Wang-Dong Zhang; Wen-Hui Wang; Ji-Xing Liu (Aquaculture, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Identification of quinoa B3 gene family and its expression pattern in response to low temperature stress - Lingyuan Zhang; Yanbo Xia; Guofei Jiang; Xuqin Wang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Corrigendum to “Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain” [Aquaculture, Volume 586, Part 2, 15 February 2025, 741875] - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Renewable intelligent superwetting biomass-based catalyst for harmless degradation of neonicotinoids with different polarities - Ruimeng Han; Shan Peng; Chunfang Zhang; Lei Wang; Xiaoyu Ji; Huanhuan Dong; Lianshan Li; Xiaoxin Chen (Journal of Cleaner Production, 2025)

Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Comparative analysis of twin-screw pressing and blending methods for walnut oleosome extraction: Yield, physical stability, and functionalities - Yu Peng; Ziming Shan; Wanqing Jia; Mo Li; Xin Wen; Yuanying Ni (Journal of Food Engineering, 2025)

Microbes: Drivers of Chenpi manufacturing, biotransformation, and physiological effects - Yanjiao Fu; Chao Wang; Zhipeng Gao; Yanfang Liao; Mingfang Peng; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Chemistry, 2025)

Gelatin-based composite film integrated with nanocellulose and extract-metal complex derived from coffee leaf for sustainable and active food packaging - Fangfei Sun; Juan Zhao; Peng Shan; Kun Wang; Hui Li; Lincai Peng (Food Hydrocolloids, 2025)

Sulfur metabolism and response to light in Ulva prolifera green tides - Lu Han; Yu Xin; Jinyan Wang; Pei-Feng Li; Tao Liu; Shan-Shan Duan; Chun-Ying Liu; Gui-Peng Yang (Environmental Pollution, 2025)

Exposure to perchlorate and cardiovascular disease in China: A community-based cross-sectional study and benchmark dose estimation - Lei King; Lili Xia; Juan Chen; Wanyi Li; Qiang Wang; Yue Huang; Pei Wang; Xiaoling Liang; Yonggang Li; Liangkai Chen; Zhilei Shan; Xiaolin Peng; et al. (Environmental Pollution, 2025)

Unraveling the role of pyrolysis temperature in biochar-mediated modulation of soil microbial communities and tobacco bacterial wilt disease - Shichen Li; Linyuan Yang; Tao Jiang; Waqar Ahmed; Fupeng Mei; Jinhao Zhang; Tao Zhang; Yingfen Yang; Xiaoci Peng; Qu Shan; Dexiang Luo; Zhengxiong Zhao (Applied Soil Ecology, 2025)

Shelterbelt influence on soil microbial carbon and phosphorus limitation in farmland: Implications for soil health - Peng He; Xuechen Yang; Zhiming Zhang; Shan-Shan Dai; Mengyang You; William R. Horwath; Peng Zhang; Wenjie Wang; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2025)

Inhibition of fish rhabdovirus demonstrates application prospect of two methylimidazole phenylpropanoid-based small molecules in aquaculture - Tian-Xiu Qiu; Huan Wang; Yang Hu; Li-Peng Shan; Guang-Lu Liu; Lei Liu; Jiong Chen (Aquaculture, 2025)

Effects of bicarbonate on antioxidant, immune, osmolytic and metabolic capabilities of Scylla paramamosain - Chenxi Che; Yuntao Li; Kangxiang Qin; Ziwei Fan; Wenjun Li; Shan Gao; Peng Yang; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Effect of thermal pretreatments on the quality attributes and irradiation markers of sesame oil extracted from sesame seeds without and with gamma irradiation - Peng-fei Xiang; Zhen-shan Zhang; Wu Le; Yun-Yi Wei; Bing-Zheng Li (Food Chemistry, 2025)

Nobiletin, an activator of the pyruvate kinase isozyme M1/M2 protein, upregulated the glycolytic signalling pathway and alleviated depressive-like behaviour caused by artificial light exposure at night in zebrafish - Meng-ling Zhang; Xiao-peng Li; Li-fang Gao; Jian Liu; Zi-jun Bi; Yu-han Miao; Yang Shan; Huan-ling Yu (Food Chemistry, 2025)

Bifunctional Nanocellulose@MOF composite aerogel for selective fluorescent detection and efficient removal of tetracycline - Zifei Yan; Liucheng Meng; Shan Jiang; Yuqing Deng; Jianfeng Xi; Lei Zhang; Peng Li; Huining Xiao; Weibing Wu (Carbohydrate Polymers, 2025)

Dynamics of nitrogen mineralization and nitrogen cycling functional genes in response to soil pore size distribution - Danni Li; Yi Li; Shuihong Yao; Hu Zhou; Shan Huang; Xianlong Peng; Yili Meng (European Journal of Soil Biology, 2024)

Genome Mining Analysis Uncovers the Previously Unknown Biosynthetic Capacity for Secondary Metabolites in Verrucomicrobia - Xue Di; Peng Li; Jingxuan Wang; Vincent Nowak; Shuai Zhi; Meiling Jin; Liwei Liu; Shan He (Marine Biotechnology, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Unveiling the toxicological effects and risks of prometryn on red swamp crayfish (Procambarus clarkii): Health assessments, ecological, and molecular insights - Lang Zhang; Ziwei Song; Li He; Shan Zhong; Xiaoqian Ju; Hang Sha; Jing Xu; Qiuying Qin; Jie Peng; Hongwei Liang (Science of The Total Environment, 2024)

A coumarin derivative C7 exhibits antiviral activity against WSSV by reducing phosphatidylcholine content in shrimp - Tian-Xiu Qiu; Xu Zhang; Yang Hu; Lei Liu; Li-Peng Shan; Jiong Chen (Fish & Shellfish Immunology, 2024)

A newly identified secretory phospholipase A2 group XIIA homolog (LcPLA2XIIA) in Larimichthys crocea exhibits antimicrobial and antitumor activities - Shouhu Li; Chuang Qin; Shi-Ming Peng; Ya-Bing Wang; Yuan Wang; Xiao-Shan Wang; Jian-Gao Shi; Xin-Cang Li (Fish & Shellfish Immunology, 2024)

Native polycyclic aromatic hydrocarbons (PAHs) in coal and its preparation products—A mixed source of environmental contamination - Shan Li; Ziqi Xu; Peng Wu; Shuquan Zhu; Handong Liang (Environmental Pollution, 2024)

The role of urban green space landscape patterns in the synergistic prevention of PM2.5 and ozone pollution: A case study in Shenyang city, China - Yu Li; Leichang Huang; Siwen Li; Min Cao; Peng Tan; Qiaochu Wang; Huan Meng; Shan Yin; Weikang Zhang (Atmospheric Pollution Research, 2024)

Exogenous Glutathione Enhances Salt Tolerance in Kenaf by Mediating Modulation of Oxidative Stress Response and DNA Methylation - Shan Cao; Guowang Liang; Lixia Zhang; Jiao Pan; Ru Li; Peng Chen (Journal of Plant Growth Regulation, 2024)

Acinetobacter corruptisaponis sp. nov., Isolated from a Spoiled Bath Lotion - Ying-Si Wang; Gang Zhou; Hong-Bing Tao; Lei Gao; Bao-Zhu Fang; Xiu-Jiang Yang; Hong Peng; Xia Wen; Xiao-Mo Huang; Jie Wang; Wen-Jun Li; Qing-Shan Shi; et al. (Current Microbiology, 2024)

Microplastics stress alters microorganism community structure and reduces the production of biogenic dimethylated sulfur compounds - Qian Liu; Xu‐Xu Gao; Yan Li; Yong Jiang; Juan Yu; Shan‐Shan Liu; Xiao‐Ping Lang; Gui‐Peng Yang (Limnology and Oceanography, 2024)
Dimethylsulfoniopropionate (DMSP) is a plentiful organic sulfur metabolite and the primary precursor for dimethyl sulfide (DMS), which plays a crucial role in global sulfur cycling, the formation of clouds, and cooling the warming earth. The origin and fate of DMSP are intricately linked to marine microorganisms, making the variation of the microorganism community crucial for DMSP dynamics. Nonetheless, the impact of pervasive marine microplastics on microorganisms and processes related to DMSP synthesis and degradation remains insufficiently investigated. To bridge this gap, a 14‐d deck‐based microcosm experiment was conducted, revealing that microplastics significantly altered the composition of microorganism communities and dramatically inhibited the release of DMS and DMSP. Furthermore, multivariate analysis demonstrated that the variations both in environmental variables and microorganism communities caused by microplastics were forcing factors in reducing DMS and DMSP release. In addition, the predicted function of the bacterial community showed a significant reduction in the presence of dddP and dmdA genes when exposed to microplastics, which directly disrupted both the demethylation and cleavage pathways of DMSP. These results indicate that the release of DMS and DMSP in marine ecosystems can be significantly affected by microplastics through influencing microorganisms. Thus, it is imperative to conduct research on controlling the synthesis and degradation of DMSP in the ocean, particularly in response to these environmental pollution issues. Such research can help discern new patterns from specific phenomena and identify crucial processes.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sesquiterpene lactones from Tithonia diversifolia with ferroptosis-inducing activities - Ao-Xue Ding; Yi-Ming Shan; Chen-Yue Li; Guo-Qing Qin; Tong Chen; Qing Wang; Xiang-Gang Hu; Peng-Ju Guo; Hai-Jun Yu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

Citrus aurantium L. 'Daidai' physiological premature fruit drop relieves obesity in high-fat-diet-fed mice via modulating lipid metabolism and gut microbiota - Mingfang Peng; Chao Wang; Zhipeng Gao; Fuhua Fu; Gaoyang Li; Donglin Su; Lvhong Huang; Jiajing Guo; Yang Shan (Food Bioscience, 2024)

Assessing health risks from bioaccessible PM2.5-bound toxic metals in Nanchang metro: Implications for metro workers and emissions control - Shan Huang; Minglei Han; Peixian Chen; Weiwei Feng; Guobo Li; Hongxiang Zhang; Honggen Peng; Ting Huang (Environmental Research, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

Efficient bioremediation of multiple steroid hormones by halotolerant 17β-hydroxysteroid dehydrogenase derived from moderately halophilic Pontibacillus chungwhensis HN14 - Haichen Yang; Zhihui Qian; Shan Zhang; Tao Peng; Jin Li; Shanshan Meng; Aihua Mao; Zhong Hu (World Journal of Microbiology and Biotechnology, 2024)

Seed priming using different agents can alleviate salt stress in kenaf (Hibiscus cannabinus L.) by activating antioxidant system and related genes expression - Renxue Li; Dengjie Luo; Muzammal Rehman; Xin Li; Caijin Wang; Shan Cao; Guofeng Xu; Meng Wang; Canni Chen; Jingzhi Nie; Ru Li; Tao Chen; et al. (Physiology and Molecular Biology of Plants, 2024)

Mechanistic Insights and Potential Therapeutic Implications of NRF2 in Diabetic Encephalopathy - Xin Cheng; Yejun Tan; Hongli Li; Zhen Zhang; Shan Hui; Zheyu Zhang; Weijun Peng (Molecular Neurobiology, 2024)

Brain state and dynamic transition patterns of motor imagery revealed by the bayes hidden markov model - Yunhong Liu; Shiqi Yu; Jia Li; Jiwang Ma; Fei Wang; Shan Sun; Dezhong Yao; Peng Xu; Tao Zhang (Cognitive Neurodynamics, 2024)

Alarming and calming: Dual functions of S100A9 on Mycoplasma gallisepticun infection in avian cells - Yingjie Wang; Mengyun Zou; Jin Liu; Qiao Guo; Shan Lv; Chunyu Chen; Tengfei Wang; Wenqing Zhao; Shiying Li; Xiuli Peng (Veterinary Microbiology, 2024)

Effects of zein extractions on the structural properties of SPI-zein composite gels: Implications for gluten-free plant-based products - Yu Peng; Yuqing Wu; Ziming Shan; Mo Li; Xin Wen; Yuanying Ni (Food Chemistry, 2024)

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Sodic adakitic granites in the East Kunlun Orogen, China: Partial melting of ultrahigh-pressure metamorphic terranes during continental collision - Lei Qin; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Li-Qun Dai; Gang Wen; You-Shan Xia; Yao Zhou (Chemical Geology, 2024)

Assembly mechanism of microbial community under different seasons in Shantou sea area - Peng Zheng; Aihua Mao; Shanshan Meng; Fei Yu; Shan Zhang; Jingsheng Lun; Jin Li; Zhong Hu (Marine Pollution Bulletin, 2024)

Artificial phytoremediation solar interface evaporator for efficient heavy metal salt separation and saline soil remediation - Yaping Xu; Chenyang Dang; Xiangkun Elvis Cao; Yunteng Cao; Jiu Huang; Yuxiang Xu; Minghui Shan; Rui Liu; Peng Li; Guiyin Xu; Meifang Zhu (Journal of Environmental Chemical Engineering, 2024)

LithoSegNet: Regional attention-based deep fusion of multi-scale and cross-stage features for real-time lithology segmentation - ZhenHao Xu; Heng Shi; Peng Lin; Shan Li (International Journal of Rock Mechanics and Mining Sciences, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

A recombinase polymerase amplification–SYBR Green I assay for the rapid and visual detection of Brucella - Jiang Chang; Nan Wang; Jun-Peng Zhan; Shi-Jun Zhang; De-Ying Zou; Feng Li; Ying Zhang; Yan-Song Li; Pan Hu; Shi-Ying Lu; Zeng-Shan Liu; Hong-Lin Ren (Folia Microbiologica, 2024)

Application of airborne gamma-ray spectrometry in geological lithology mapping—a case study of a region in the Qinling Mountains, China - Yongzai Xi; Guixiang Liao; Yongbo Li; Junjie Liu; Shan Wu; Ning Lu; Peng He (Acta Geophysica, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Pyrite from acid mine drainage promotes the removal of antibiotic resistance genes and mobile genetic elements in karst watershed with abundant calcium carbonate - Qian Zhang; Yuhua Li; Xinyi Peng; Xue Bai; Lishan Zhang; Shan Zhong; Xiaohua Shu (Journal of Hazardous Materials, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

DNA Methylome Provide New Insights into the Physiological-Molecular Regulation of Salt Stress in Kenaf Using 5-azaC Pretreatment - Zengqiang Li; Dengjie Luo; Shan Cao; Samavia Mubeen; Muzammal Rehman; Caijin Wang; Gang Jin; Ru Li; Tao Chen; Peng Chen (Journal of Soil Science and Plant Nutrition, 2024)

Prediction of critical heat flux in rod bowing geometries by coupled subchannel analysis and mechanistic model - Junliang Guo; Jianqiang Shan; Li Jiang; Yujiao Peng; Shan Zhou; Miao Gui (Annals of Nuclear Energy, 2024)

Atmospheric CO2 in the megacity Hangzhou, China: Urban-suburban differences, sources and impact factors - Yuanyuan Chen; Yanran Lu; Bing Qi; Qianli Ma; Kunpeng Zang; Yi Lin; Shuo Liu; Fengmei Pan; Shan Li; Peng Guo; Lihan Chen; Wengang Lan; et al. (Science of The Total Environment, 2024)

Humidity-adjustable functional gelatin hydrogel/ethyl cellulose bilayer films for active food packaging application - Peng Shan; Kun Wang; Fangfei Sun; Yongshi Li; Liping Sun; Hui Li; Lincai Peng (Food Chemistry, 2024)

Maximizing potato tuber yields and nitrogen use efficiency in semi-arid environments by precision fertilizer depth application - Nanhai Zhang; Haiqiang Luo; Heng Li; Mingwei Bao; Enke Liu; Weixing Shan; Xiaolong Ren; Zhikuan Jia; Kadambot H.M. Siddique; Peng Zhang (European Journal of Agronomy, 2024)

Waste cigarette butts-templated synthesis of in-situ graphitic carbon-doped ZnO fibers boosting dual-selectivity NO2/butanone at different temperatures - Zhao-Qi Cui; Ze Wei; Cong Chen; Yuan-Yuan Sun; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Novel insights into the protective effects of leonurine against acute kidney injury: Inhibition of ER stress-associated ferroptosis via regulating ATF4/CHOP/ACSL4 pathway - Ran Cheng; Xiaowan Wang; Lihua Huang; Zhisheng Lu; Aijun Wu; Shan Guo; Chuang Li; Wei Mao; Ying Xie; Peng Xu; Ruimin Tian (Chemico-Biological Interactions, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Taxonomic status of hares ( Lepus spp.) in Xinjiang, China (Lagomorpha: Leporidae): An integrative approach - Wen‐Juan Shan; Zu‐Rui Li; Hui‐Ying Dai; Peng‐Cheng Dong; Yu‐Cong Zhang (Zoologica Scripta, 2024)
The taxonomic status and interspecies relationships of hares (genus Lepus ) in Xinjiang, China, remain ambiguous owing to extremely similar external morphologies, introgressive hybridization between species and a lack of molecular genetic records. In this study, a total of 154 hare specimens were used to clarify their taxonomic status. Based on multiple lines of evidence, including observations and comparisons of external morphological characteristics, skull morphometrics and genome‐wide single nucleotide polymorphism (SNP) datasets, four hare species were recognised. Lepus yarkandensis and Lepus timidus , which have obvious morphological characteristics, were identified as two distinct species, as previously reported. Combining the integrated morphological and molecular datasets with the relevant literature, we proposed suggestions on the classification of the more controversial hares. Due to molecular and morphological similarities, hares in northern and central Xinjiang were divided into two subspecies of Lepus tolai , namely, Lepus tolai lehmanni and Lepus tolai centrasiaticus . Despite similar external morphological characters, hares in the southwest Pamir Plateau and its surroundings can be distinguished from L. tolai by differences in skull morphology and genetic divergence and were, therefore, considered a subspecies of Lepus tibetanus , Lepus tibetanus pamirensis . Furthermore, we found that hybridization and introgression occurred between sympatric or parapatric hares, especially between L. yarkandensis and L. tibetanus pamirensis , L. yarkandensis and L. tolai centrasiaticus , and L. tolai lehmanni and L. timidus .

Initiation mechanism of shallow loess slope sliding under coupling effect of train vibration and rainfall - Kai Han; Jiading Wang; Shan Li; Peng Xiao; Dengfei Zhang; Fei Wang; Haoyu Dong (Soil Dynamics and Earthquake Engineering, 2024)

Ultra-deep oxidative desulfurization of high sulfur liquid fuels using W/W2C heterostructured nanoparticles embedded on N-doped graphene - Yefeng Liu; Peng Zuo; Xiaojie Yin; Chuan Li; Fuyan Zhao; hongxing Shi; Jing Li; Yang Han; nannan Wang; Xinxi Bai; Yumeng Tao; Shan Jiang; et al. (Journal of Environmental Chemical Engineering, 2024)

A comprehensive review on the characteristics and kinetics of freshwater separation by hydrate-based method: Current progress, challenges and perspectives - Xuemin Zhang; Jiajing He; Tao Shan; Qingqing Liu; Qing Yuan; Jinping Li; Qingbai Wu; Peng Zhang (Desalination, 2024)

Genomic data and ecological niche modeling reveal an unusually slow rate of molecular evolution in the Cretaceous Eupteleaceae - Kun-Li Xiang; Sheng-Dan Wu; Lian Lian; Wen-Chuang He; Dan Peng; Huan-Wen Peng; Xiao-Ni Zhang; Hong-Lei Li; Jia-Yu Xue; Hong-Yan Shan; Gui-Xia Xu; Yang Liu; et al. (Science China Life Sciences, 2024)

Classic Famous Prescription Kai-Xin-San Ameliorates Alzheimer’s Disease via the Wnt/β-Catenin Signaling Pathway - Xiaoxiao Shan; Shujie Lv; Peng Huang; Wei Zhang; Chuanshan Jin; Yuanxu Liu; Yangyang Li; Yong Jia; Xiaoqin Chu; Can Peng; Caiyun Zhang (Molecular Neurobiology, 2024)

Potential application of a small molecule compound in aquaculture against WSSV infection by maintaining the homeostasis of intestinal microbiota - Li-Peng Shan; Xu Zhang; Yang Hu; Lei Liu; Jiong Chen (Aquaculture, 2024)

The infectious haemorrhagic syndrome virus (IHSV) from rice-field eel (Monopterus albus): Isolation, genome sequence, cross-infection and induced-immune response in Chinese perch (Siniperca chuatsi) - Shan Nan Chen; Hui Jun Huo; Yong Jin; Xue Yun Peng; Bo Li; Xiang Yang Wu; Zhi Wei Zhang; Jing Yun Tian; Qian Wang; Nan Li; Lan Hao Liu; P. Nie (Aquaculture, 2024)

Biodegradation of polyethylene terephthalate by Tenebrio molitor: Insights for polymer chain size, gut metabolome and host genes - Lei He; Shan-Shan Yang; Jie Ding; Cheng-Xin Chen; Fan Yang; Zhi-Li He; Ji-Wei Pang; Bo-Yu Peng; Yalei Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Journal of Hazardous Materials, 2024)

Novel insights into aerobic 17β-estradiol degradation by enriched microbial communities from mangrove sediments - Shan Zhang; Xueying Ye; Xianbin Lin; Xiangwei Zeng; Shanshan Meng; Wenqi Luo; Fei Yu; Tao Peng; Tongwang Huang; Jin Li; Zhong Hu (Journal of Hazardous Materials, 2024)

Physiological, transcriptome and gene functional analysis provide novel sights into cadmium accumulation and tolerance mechanisms in kenaf - Shan Cao; Meng Wang; Jiao Pan; Dengjie Luo; Samavia Mubeen; Caijin Wang; Jiao Yue; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Journal of Environmental Sciences, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Electrochemical capacitance of clay minerals by diamine modification - Yi Liao; Shan-Shan Chai; Wei-Bin Zhang; Yao Yao; Jing-Lei Yang; Yi Yin; Jia-Jun Li; Ze-Qin Yang; Xue-Jing Ma; Qiang Peng (Applied Clay Science, 2024)

Design of an active-source seismic detection system based on illumination analysis and migration imaging experiments: considering the Zhuxi mining area as an example - Wen Li; Yong Chen; Shan-Hui Xu; Jiu-Peng Hu; Bao-Jin Liu; Yong-Peng Ouyang; Yin-Juan He; Ya-Li Tan; Xin-Sheng Hua; Jing-Jing Qin; Qian Li; Jia Jia (Applied Geophysics, 2024)

Morpho-physio-biochemical, molecular, and phytoremedial responses of plants to red, blue, and green light: a review - Muzammal Rehman; Jiao Pan; Samavia Mubeen; Wenyue Ma; Dengjie Luo; Shan Cao; Wajid Saeed; Gang Jin; Ru Li; Tao Chen; Peng Chen (Environmental Science and Pollution Research, 2024)

A study of typical plant growth changes in response to drainage water and salt in ditch wetland in arid area - Qian Wang; Shan Li; Liangjun Fei; Miao Wu; Runqiao Zheng; Youliang Peng; Fangyuan Shen (Science of The Total Environment, 2024)

An AIS-based deep learning model for multi-task in the marine industry - Zechen Li; Tong Liu; Xing Peng; Jinxin Ren; Shan Liang (Ocean Engineering, 2024)

In-situ sodium chloride template synthesis of γ-WO3 hollow cubes for high-sensing and dual-selective hydrazine/dibutylamine detection at different temperatures - Guo-Li Chen; Ming-Song Lv; Jing Zhang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Facilitating mitigation of agricultural non-point source pollution and improving soil nutrient conditions: The role of low temperature co-pyrolysis biochar in nitrogen and phosphorus distribution - Yufei Zhao; Zhijun Hu; Yunpeng Lu; Shengdao Shan; Haifeng Zhuang; Chenpan Gong; Xin Cui; Fuhao Zhang; Peng Li (Bioresource Technology, 2024)

Large-area nanofiber membrane of NIR photothermal Cs0.32WO3 for flexible and all-weather solar thermoelectric generation - Sheng Zhuo; Wangkai Jiang; Yu Dong Zhao; Jin-Zhuo Liu; Xinyu Zhao; Jianyong Ye; Min Zheng; Zuo-Shan Wang; Xiao-Qing Zhou; Xiao-Qiao Wang; Ying-Li Shi; Weifan Chen; et al. (Chemical Engineering Journal, 2024)

AM fungi reduce grass–legume competition by increasing nutrient access - Jiqiong Zhou; Jinchao Gong; Shan Liu; Adam B. Cobb; Gaowen Yang; Xiangjun Li; Feida Sun; Yan Peng; Yanhong Yan; Lin Liu; Xinquan Zhang (Plant and Soil, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

The antiviral activity of currently used medicinal plants in aquaculture and structure–activity relationship of their active ingredients - Yang Hu; Xu Zhang; Li‐peng Shan; Lei Liu; Jiong Chen (Reviews in Aquaculture, 2024)
Aquaculture is an important source of high‐quality protein and plays a crucial role in ensuring global food security. However, viral diseases have caused significant damage to aquaculture production, making it necessary to develop effective measures to treat them. Although drugs are commonly used to treat viral diseases, recent studies have shown that crude extracts of medicinal plants and their active ingredients have potential applications in the treatment of aquatic viral diseases. Furthermore, natural small molecule compounds from herbs could be used as lead compounds to develop more potent anti‐aquatic virus derivatives. As such, there is an urgent need to develop and apply drugs for the treatment of viral disease outbreaks in aquaculture. In this review, we summarize previous studies on the efficacy of different agents used as antiviral drugs in aquaculture, with a focus on their protective effects. Additionally, we highlight the potential of active natural compounds isolated from medicinal plants, which could serve as lead compounds for developing aquatic‐specific drugs. However, the relationship between the structure of a compound and its antiviral activity in aquaculture has not been clearly elucidated, posing a challenge for further drug optimisation. Therefore, this study also analyses the structure–activity relationship of several reported lead compounds and their derivatives in aquaculture, providing a reference for subsequent drug development efforts.

Review on image-based animals weight weighing - Yuliang Zhao; Qijun Xiao; Jinhao Li; Kaixuan Tian; Le Yang; Peng Shan; Xiaoyong Lv; Lianjiang Li; Zhikun Zhan (Computers and Electronics in Agriculture, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

The impacts of clean energy policies on air pollutants and CO2 emission reduction in Shaanxi, China - Xin Bo; Qian You; Minjie Sang; Peng Wang; Shaobo Chen; Xin Xu; Wanyue Shan; Ying Yang; Bertrand Bessagnet; Hongmei Li; Yong Xiao (Atmospheric Pollution Research, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Associating phthalate exposure during pregnancy with preschooler's FMI, ABSI and BRI trajectories via putative mechanism pathways - Hui Gao; Yi Zhang; Li-wen Chen; Hong Gan; Meng-juan Lu; Binbin Huang; Juan Tong; Meng-long Geng; Kun Huang; Cheng Zhang; Bei-bei Zhu; Shan-shan Shao; et al. (Chemosphere, 2023)

Role of Caveolin-1 on the molybdenum and cadmium exposure induces pulmonary ferroptosis and fibrosis in the sheep - Tao Zhang; Fan Yang; Xueyan Dai; Huan Liao; Huating Wang; Chengcheng Peng; Zirui Liu; Zhiyuan Li; Jiyi Shan; Huabin Cao (Environmental Pollution, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Genome-wide identification of CUC gene family and functional analysis of HcCUC1 in kenaf - Qijing Wu; Canni Chen; Jiao Yue; Samavia Mubeen; Shan Cao; Xin Li; Meng Wang; Hui Zhang; Xia Wu; Caijin Wang; Dengjie Luo; Peng Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Sources, size-resolved deposition in the human respiratory tract and health risks of submicron black carbon in urban atmosphere in Pearl River Delta, China - Yuan Liu; Lina Wu; Shan Huang; Qicong Song; Weiwei Hu; Wei Chen; Zhijun Wu; Ruiqi Man; Yao He; Wei Li; Yuwen Peng; Junwen Liu; et al. (Science of The Total Environment, 2023)

Preparation and properties of a novel pH-stable nanofiltration membrane embedded with amino-modified silicon carbide - Yu Sun; Quanji Zhu; Guanghui Li; Bo Peng; Guoling Ruan; Baotian Shan; Jia Xu (Desalination, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Economic policy uncertainty, geopolitical risks, and the heterogeneity of commodity price fluctuations in China ——an empirical study based on TVP-SV-VAR model - Guoheng Hu; Shan Liu; Guo Wu; Peng Hu; Ruiqi Li; Liujie Chen (Resources Policy, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Effects of elevated temperature and acidification on sulfate assimilation and reduction of microalgae - Qin-Dao Li; Pei-Feng Li; Shan-Shan Duan; Chun-Ying Liu; Li-Jun Xie; Gui-Peng Yang (Journal of Applied Phycology, 2023)

Discovery of a substance that enhances the immune response in Litopenaeus vannamei against WSSV: Baicalein, a major component of Scutellaria baicalensis - Li-Peng Shan; Ling Hu; Xu Zhang; Da-Wei Song; Yang Hu; Lei Liu; Jiong Chen (Aquaculture, 2023)

An online intelligent management method for wastewater treatment supported by coupling data-driven and mechanism models - Jian-Hui Wang; Du-Jiang Zhao; Wan-Shan Liao; Mohamed S. Mahmoud; Zhi-Wei Guo; Hui-Min Li; Xu Gao; Dong Feng; Long-Fei Shi; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2023)

Global spatiotemporal trend of satellite-based soil moisture and its influencing factors in the early 21st century - Chenchen Peng; Jiangyuan Zeng; Kun-Shan Chen; Zhen Li; Hongliang Ma; Xiang Zhang; Pengfei Shi; Tiantian Wang; Lu Yi; Haiyun Bi (Remote Sensing of Environment, 2023)

Physiological and DNA methylation analysis provides epigenetic insights into kenaf cadmium tolerance heterosis - Dengjie Luo; Hai Lu; Caijin Wang; Samavia Mubeen; Shan Cao; Jiao Yue; Jiao Pan; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Plant Science, 2023)

Co-chaperoning of chlorophyll and carotenoid biosynthesis by ORANGE family proteins in plants - Tianhu Sun; Peng Wang; Sombir Rao; Xuesong Zhou; Emalee Wrightstone; Shan Lu; Hui Yuan; Yong Yang; Tara Fish; Theodore Thannhauser; Jiping Liu; Michael Mazourek; et al. (Molecular Plant, 2023)

Abandoned disposable masks become hot substrates for plastisphere, whether in soil, atmosphere or water - Jianlong Li; Tianli Zhang; Xiaoling Shan; Wei Zheng; Zhenming Zhang; Zhuozhi Ouyang; Peng Liu; Xuetao Guo (Journal of Hazardous Materials, 2023)

The presence of soybean, but not soybean cropping frequency has influence on SOM priming in crop rotation systems - Shan-Shan Dai; Peng He; Meng-Yang You; Lu-Jun Li (Plant and Soil, 2023)

Comparative Physiological and Transcriptomic Analysis Provide New Insights of Crucial Pathways and Genes Regulating Kenaf Salt Tolerance - Yali Hu; Zengqiang Li; Meiqiong Tang; Dengjie Luo; Muhammad Haneef Kashif; Shan Cao; Caijin Wang; Jiao Yue; Zhen Huang; Jiao Pan; Xia Wu; Qijing Wu; et al. (Journal of Plant Growth Regulation, 2023)

Zein nanospheres assisting inorganic and organic drug combination to overcome stent implantation-induced thrombosis and infection - Hua-Jie Wang; Meng-Fei Hao; Guan Wang; Hao Peng; Fazli Wahid; Yan Yang; Lei Liang; Shan-Qin Liu; Ren-Long Li; Shu-Ying Feng (Science of The Total Environment, 2023)

A unique suit of Wuchiapingian marine red beds in central China representing a specific paleogeography and paleoclimate association - Cheng Cheng; Zi'an Shan; Mingyu Shan; Zhonglai Zhou; Bingyan Ren; Yike Chu; Shuangying Li; Dan Wang; Hongzuo Wang; Xujie Shu; Peng Qian (Marine and Petroleum Geology, 2023)

Low-temperature and dual-sensing NO2/dimethylamine sensor based on single-crystal WO3 nanoparticles-supported sheets synthesized by simple pyrolysis of spoiled WCl6 powder - Guo-Li Chen; Ming-Song Lv; Li-Li Sui; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Early 7,8-Dihydroxyflavone Administration Ameliorates Synaptic and Behavioral Deficits in the Young FXS Animal Model by Acting on BDNF-TrkB Pathway - Yu-shan Chen; Si-ming Zhang; Wei Tan; Qiong Zhu; Chao-xiong Yue; Peng Xiang; Jin-quan Li; Zhen Wei; Yan Zeng (Molecular Neurobiology, 2023)

Photolysis frequency of nitrophenols derived from ambient measurements - Yuwen Peng; Bin Yuan; Suxia Yang; Sihang Wang; Xiaoyun Yang; Wenjie Wang; Jin Li; Xin Song; Caihong Wu; Jipeng Qi; E. Zheng; Chenshuo Ye; et al. (Science of The Total Environment, 2023)

Metabolites identification of 17α-methyltestosterone mediated by Aspergillus niger RG13B1 and their cytotoxicity on cancer cells - Peng Cao; Shengqiao Luan; Wenxin Wang; Yufei Wang; Shan Wu; Gang Wang; Fangyu Yang; Chao Wang; Guobiao Liang; Dawei Li (Phytochemistry Letters, 2023)

Facile fabrication of solar-heating and Joule-heating hyperelastic MXene-modified sponge for fast all-weather clean-up of viscous crude oil spill - Zhangdi Li; Zhaoyu Shan; Qiong Tian; Xiaoming Peng; Xuejie Yue; Fengxian Qiu; Tao Zhang (Journal of Hazardous Materials, 2023)

Non-noble-metal NiS promoted charge separation and photocatalytic hydrogen evolution for ZnCdS nano-islands on spherical SiO2 - Ke Liu; Shan Yang; Wei Li; Yifan Wang; Chuanzhi Sun; Lu Peng; Hermenegildo Garcia (Fuel, 2023)

Tectonic Transformation, Magmatic Activity and Subsidence Centre Migration of Eocene Half-Grabens: A Case Study of the Northern Pearl River Mouth Basin (PRMB) in the Northern South China Sea - Guangrong Peng; Pei Liu; Weitao Chen; Zhensheng Li; Xiaomeng Wang; Zhiwei Zhang; Xuanlong Shan; Guoli Hao (Journal of Marine Science and Engineering, 2023)
The Pearl River Mouth Basin (PRMB) is located in the northern part of the South China Sea. The Palaeogene Wenchang Formation (Fm) was formed at the rift stage and contains the main source rocks. The migration of Wenchang subsidence centres in the western Zhu I Depression and northern Yangjiang-Yitong Fault Zone are controlled by tectonic transformation and partially influenced by magmatic activity. From the Eocene Wenchang (E2WC) to the Eocene and Oligocene Enping (E2+3EP) stages, the regional extension direction rotated clockwise from NW–SE to S–N, and the strike of the regional strike-slip fault was NW–SE. The subsidence centres of the Wenchang Fm in the western subsags of the Zhu I Depression migrated to the Beiweitan Fault in a convergent way. Magmatic activity at the E2WC stage developed mostly along the central edge of the subsags. Local subsidence migrated to the side of the basin-controlling faults. The migration characteristics of the subsidence centre of the Wenchang Fm in each subsag are complex in the northern Yangjiang-Yitong Fault Zone. There was no magmatic activity at the E2WC to E2+3EP stage of the Enping 27 subsag, and the subsidence centre migrated eastwards, which is basically consistent with the migration pattern of the Enping sag. In the eastern Yangjiang sag, the strike of the subsags was ENE. The angle between the extensional direction and subsag strike at the E2WC to E2+3EP stage first increased and then decreased. Magmatic activity at the E2WC stage mostly developed in the subsags. Tectonic transformation and magmatic activity at the E2WC stage led to subsidence centre migration from the Enping 21 subsag to the Enping 20 subsag northwest. From the end of the E2WC stage to the E2+3EP stage, magmatic activity developed at the subsag margins, which resulted in severe denudation. Research on the entire area indicates that tectonic transformation controls subsidence centre migration. Magmatic activity influences the migration of subsidence centres locally or controls this process through tectonic transformation.

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

Comprehensive analysis reveals the underlying mechanism of arbuscular mycorrhizal fungi in kenaf cadmium stress alleviation - Jiao Pan; Shan Cao; Guofeng Xu; Muzammal Rehman; Xin Li; Dengjie Luo; Caijin Wang; Wangqiang Fang; Huiping Xiao; Changjun Liao; Peng Chen (Chemosphere, 2023)

Granitic record of the assembly of the Asian continent - Tao Wang; Ying Tong; He Huang; Hongrui Zhang; Lei Guo; Zhengxiang Li; Xiaoxia Wang; Bruce Eglington; Shan Li; Jianjun Zhang; Tatiana V. Donskaya; Oleg Petrov; et al. (Earth-Science Reviews, 2023)

Accidental acquisition of a rescued Japanese encephalitis virus with unspliced introns in the viral genome when using an intron-based stabilization approach - Ying Huang; Hongshan Xu; Shan Liu; Jiansheng Lu; Lili Jia; Yuhua Li; Rong Wang; Peng Yang; Yongxin Yu; Zhixin Yang (Archives of Virology, 2023)
The intron-based stabilization approach is a very useful strategy for construction of stable flavivirus infectious clones. SA 14 -14-2 is a highly attenuated Japanese encephalitis (JE) live vaccine strain that has been widely used in China since 1989. To develop safe and effective recombinant vaccines with SA 14 -14-2 as a backbone vector, we constructed the DNA-based infectious clone pCMW-JEV of SA 14 -14-2 using the intron-based stabilization approach and acquired the rescued virus rDJEV, which retained the biological properties of the parental virus. Unexpectedly, a rescued virus strain with altered virulence, designated rHV-DJEV, was accidentally acquired in one of the transfection experiments. rHV-DJEV showed up to 10 5 -fold increased neurovirulence compared with the SA 14 -14-2 parental strain. Genome sequencing showed that the inserted introns were still present in the genome of rHV-DJEV. Therefore, we think that the intron-based stabilization approach should be used with caution in vaccine development and direct iDNA immunization.

Toxicity of ceria nanoparticles to the regeneration of freshwater planarian Dugesia japonica: The role of biotransformation - Changjian Xie; Xiaowei Li; Lisha Hei; Yiqing Chen; Yuling Dong; Shujing Zhang; Shan Ma; Jianing Xu; Qiuxiang Pang; Iseult Lynch; Zhiling Guo; Peng Zhang (Science of The Total Environment, 2023)

A repeated dose 28-day oral toxicity study of sodium dehydroacetate (DHA-S) in Wistar rats - Hong-ju Du; Guo-hui Tong; Jun-yu Ning; Shan Gao; Qing Yang; Ying Feng; Peng Zhang; Wei Zhang; Hai-ming Jing; Guo-jun Li (Regulatory Toxicology and Pharmacology, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Study on the variations of extractable polycyclic aromatic hydrocarbons in lignite and semi-coke - Shan Li; Mengqian Lu; Peng Wu; Shuquan Zhu; Cai Tie; Xuanhe Zhao; Handong Liang (Fuel, 2023)

Multifunctional polyether block amides/carbon nanostructures piezoresistive foams with largely linear range, enhanced and humidity-regulated microwave shielding - Xueyun Li; Shan Li; Minghui Wu; Zhengsheng Weng; Qian Ren; Peng Xiao; Long Wang; Wenge Zheng (Chemical Engineering Journal, 2023)

SBA-15-supported ultrastable Mo2N@CN catalysts for hydrodeoxygenation of guaiacol - Fan Wang; Chenglong Wen; Mohong Lu; Peng Zhang; Jie Zhu; Mingshi Li; Yuhua Shan; Chunshan Song (Biomass and Bioenergy, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

Study on characteristics of pressure relief by roof cutting under nonpillar-mining approach - Jianning Liu; Manchao He; Shan Guo; Jieyu Li; Peng Zhou; Zhen Zhu (Bulletin of Engineering Geology and the Environment, 2022)

Associations of long-term ambient air pollution and traffic-related pollution with blood pressure and hypertension defined by the different guidelines worldwide: the CHCN-BTH study - Bingxiao Li; Han Cao; Kuo Liu; Juan Xia; Yanyan Sun; Wenjuan Peng; Yunyi Xie; Chunyue Guo; Xiaohui Liu; Fuyuan Wen; Fengxu Zhang; Guangliang Shan; et al. (Environmental Science and Pollution Research, 2022)

Nanoscale storage encryption: data storage in synthetic DNA using a cryptosystem with a neural network - Yue Teng; Shan Yang; Liyan Liu; Ruicun Liu; Yaofeng Chen; Jinyu Li; Qian Yang; Tuoyu Liu; Yujun Cui; Peng Cheng; Shengqi Wang (Science China Life Sciences, 2022)

Alternate freezing and thawing enhanced the sediment and nutrient runoff loss in the restored soil of the alpine mining area - Fa-Yong Li; Ren-jie Luo; Yong-jun You; Xue-fei Hu; Xiao-yan Qian; Peng-yan Zhang; Shan Wang; Guo-yu Li; Mohamed Eltohamy Kamel (Journal of Mountain Science, 2022)

An adaptive data cleaning framework: a case study of the water quality monitoring system in China - Zeng Chen; Peng Jiang; Jun Liu; Song Zheng; Zhenyu Shan; Zhihua Li; Huan Xu; Igor V. Bychkov; Alexei E. Hmelnov (Hydrological Sciences Journal, 2022)

Integrated comparison of growth and oxidative stress induced by tylosin in two freshwater algae Chlorella vulgaris and Raphidocelis subcapitata - Denglong Lu; Zhihua Ma; Jianglin Peng; Yibo Zhang; Shan Liu; Qi Li (Ecotoxicology, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

Natural ingredient paeoniflorin could be a lead compound against white spot syndrome virus infection in Litopenaeus vannamei - Yang Hu; Lei Liu; Li‐peng Shan; Jiong Chen (Journal of Fish Diseases, 2022)
White spot syndrome virus (WSSV) is an important pathogen causing high mortality in the shrimp industry in aquaculture, yet there is no treatment available to date. In order to find a treatment against WSSV infection, this study examined the anti‐WSSV activity of eight natural compounds using shrimp larvae as a model. Among the eight compounds, paeoniflorin showed the most obvious anti‐WSSV effect, with a maximum protection efficiency of WSSV‐infected shrimp >60% at 100 μM. Furthermore, pretreatment and post‐treatment experiments revealed that paeoniflorin could prevent and treat WSSV infection in shrimp. The antiviral activity of paeoniflorin in aquaculture water decreased rapidly with time, and the results showed that the stable anti‐WSSV activity of paeoniflorin could only remain in water for 1 day. Thus, the dosing pattern of continuous medication changes was evaluated. Obviously, in the model of continuous change of paeoniflorin, WSSV copy numbers in the virus‐treated shrimp group still progressively increased, while the virus content in WSSV paeoniflorin ‐treated group continued to decrease. Interestingly, paeoniflorin inhibited horizontal transmission of WSSV to a certain extent. Notably, paeoniflorin significantly increased the expression of antimicrobial peptides of shrimp to resist WSSV. In conclusion, paeoniflorin has the potential to protect shrimp against WSSV.

Antiviral activity of esculin against white spot syndrome virus: A new starting point for prevention and control of white spot disease outbreaks in shrimp seedling culture - Li‐Peng Shan; Xu Zhang; Yang Hu; Lei Liu; Jiong Chen (Journal of Fish Diseases, 2022)
White spot syndrome virus (WSSV) is a pathogenic and threatening virus in shrimp culture for which there is no effective control strategy. Finding antiviral lead compounds for the development of anti‐WSSV drugs is urgent and necessary; in this study, esculin from 12 monomeric compounds exhibited an excellent anti‐WSSV activity. The results showed that esculin increased the survival rate of WSSV‐infected shrimps by 59% and reduced the virus copy number in vivo over 90% at 100 μM. In the pre‐treatment and post‐treatment experiments, esculin could prevent and treat WSSV infection. Compared with the control group, the virus copy number decreased by 30% after 6 h of esculin pre‐incubation with WSSV particles and inhibited horizontal transmission of WSSV to a certain extent. Considering that the antiviral activity of esculin was stable in the aquacultural water for 2 days, we evaluated the dosing pattern of continuous medication changes. Obviously, the survival rate of WSSV‐infected shrimps was 0% at 108 h when no esculin exchange was made, while at 120 h the survival rate was over 40% at continuous medicine changes. In addition, esculin significantly increased the expression of antimicrobial peptides and thus improved the ability of shrimp to resist WSSV. Overall, our findings suggest that esculin has the potential to be developed into an anti‐WSSV medicine.

A genome-wide association study reveals that the cytochrome b5 involved in seed reserve mobilization during seed germination in rice - Zhibo Huang; Jifeng Ying; Liling Peng; Shan Sun; Chengwei Huang; Can Li; Zhoufei Wang; Yongqi He (Theoretical and Applied Genetics, 2021)

Memory regulation in feeding habit transformation to dead prey fish of Chinese perch (Siniperca chuatsi) - Linjie Shi; Jiao Li; Xu-Fang Liang; Shan He; Yaqi Dou; Jian Peng; Wenjing Cai; Hui Liang (Fish Physiology and Biochemistry, 2021)

Adaptation of AMPK-mTOR-signal pathways and lipid metabolism in response to low- and high-level rapeseed meal diet in Chinese perch (Siniperca chuatsi) - Jiao Li; Xu-Fang Liang; Muhammad Shoaib Alam; Haocan Luo; Yanpeng Zhang; Binbin Peng; Qianqian Xiao; Zhilu Zhang; Liwei Liu; Shan He (Journal of Comparative Physiology B, 2021)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

Recreational Nitrous Oxide Abuse: Prevalence, Neurotoxicity, and Treatment - Yuanyuan Xiang; Lei Li; Xiaotong Ma; Shan Li; Yuan Xue; Peng Yan; Meijie Chen; Junwei Wu (Neurotoxicity Research, 2021)

Black phosphorus nanosheets and docetaxel micelles co-incorporated thermoreversible hydrogel for combination chemo-photodynamic therapy - Ruirui Li; Linwei Shan; Yanan Yao; Feifei Peng; Shanshan Jiang; Dandan Yang; Guixia Ling; Peng Zhang (Drug Delivery and Translational Research, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Astragaloside IV inhibits palmitic acid-induced apoptosis through regulation of calcium homeostasis in mice podocytes - Yingjun Zang; Shuang Liu; Aili Cao; Xiangyu Shan; Wenjuan Deng; Zhijun Li; Hao Wang; Yunman Wang; Li Wang; Wen Peng (Molecular Biology Reports, 2021)
Loss of podocytes is a hallmark of diabetic nephropathy, and a growing body of evidence indicates that podocytes are susceptible to palmitic acid (PA). We have previously shown that AS-IV inhibited PA-induced podocyte apoptosis by activating sarcoendoplasmic reticulum Ca 2+ ATPase (SERCA), which indicate calcium regulation may involve in the process. Immunofluorescence staining, Western blot and flow cytometry were used to measure the protective efficacy of AS-IV to ameliorate PA-induced ER stress and podocyte apoptosis. Meanwhile, AS-IV inhibited cytochrome c release, decreased mitochondrial membrane potential, accompany with the depletion of endoplasmic reticulum Ca 2+ and elevation of cytosolic and mitochondrial Ca 2+ . Sequestration of cytosolic calcium with BAPTA-AM limited the response of podocyte apoptosis, while during the process the effect of AS-IV was also restrained. In contrast, elevation of cytosolic calcium with calcium ionophore ionomycin was depressed by AS-IV addition. Furthermore, inhibiting TRPC6 expression with SKF96365 or TRPC6 siRNA counteracted the beneficial effect of AS-IV. Our study provides further evidence to conclude the inhibitory effect of AS-IV to podocyte apoptosis is Ca 2+ -dependent. And the efficacy correlates with inhibiting TRPC6-mediated Ca 2+ influx, and then cellular Ca 2+ disturbance was coordinated.

New nitrogen-containing metabolites from cultures of rice false smut pathogen Villosiclava virens - Ali Wang; Peng Li; Peipei Han; Gan Gu; Tijiang Shan; Daowan Lai; Ligang Zhou (Natural Product Research, 2021)

Valine acts as a nutritional signal in brain to activate TORC1 and attenuate postprandial ammonia-N excretion in Chinese perch (Siniperca chuatsi) - Jie Wang; Xu-Fang Liang; Shan He; Yan-Peng Zhang; Jiao Li; Kang Huang; Lin-Jie Shi; Ping Ren (Fish Physiology and Biochemistry, 2020)

Design of a downlink algorithm for rotary steering (logging while drilling) systems - Liang Yao; Wang Mei-Shan; Liu Peng; Zhu Bo; Ma Li; Sun Yan (Applied Geophysics, 2020)

Evaluation of soil erosion and sediment deposition rates by the 137Cs fingerprinting technique at different hillslope positions on a catchment - Yanqing Li; Zhongcheng Jiang; Yang Yu; Zhijie Shan; Funing Lan; Xiangfei Yue; Peng Liu; Yeboah Gyasi-Agyei; Jesús Rodrigo-Comino (Environmental Monitoring and Assessment, 2020)

The Phylogeny and Functional Characterization of Peanut Acyl-ACP Thioesterases - Zhenying Peng; Hui Zhang; Haiying Tian; Lei Shan; Zhimeng Zhang; Hong Ding; Wenwei Gao; Xinguo Li (Journal of Plant Growth Regulation, 2020)
Fatty acyl-acyl thioesterases (FATs), which hydrolyze the thioester bond linking acyl chains to an acyl carrier protein, thereby terminating their elongation, contribute significantly to the fatty acid (FA) content and composition of seed storage lipids. The peanut ( Arachis hypogaea L.) genome was found to harbor 21 FAT ( AhFAT ) genes, distributed over 12 of the 20 chromosomes. The length of their predicted translation products varied from 74 to 415 residues, and all but one included the 1–2 Acyl-ACP_TE conserved domains. All of the coding sequences were interrupted by at least one intron, with the exon number ranging from two to 12, and five of the genes were liable to alternative splicing. When the RNA-Seq platform was used to assess the transcriptional behavior of the 21 AhFAT genes, transcription of only 13 was detectable in samples of root, leaves, and developing seed; among these, six were transcribed throughout the plant, three were root-specific and one was leaf-specific. A detailed analysis of a pair of homologous AhFATs showed that the coding region of each was split into six exons and that both were transcribed in all of the plant organs surveyed (although the intensity of their transcription was not the same in immature seed). The product of both genes was deposited in the chloroplast outer membrane. The constitutive expression of these genes in either yeast or Arabidopsis thaliana increased the FA content, especially that of saturated FAs. In peanut genome, 21 AhFAT genes were found and two of them were transformed into yeast and Arabidopsis for function identification. Results showed that overexpression of these two genes could increase the FA content, especially the saturated FAs content.

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

The Family of Peanut Fatty Acid Desaturase Genes and a Functional Analysis of Four ω-3 AhFAD3 Members - Zhenying Peng; Jian Ruan; Haiying Tian; Lei Shan; Jingjing Meng; Feng Guo; Zhimeng Zhang; Hong Ding; Shubo Wan; Xinguo Li (Plant Molecular Biology Reporter, 2020)
The synthesis of α-linolenic acid (ALA) requires the activity of ω-3 fatty acid desaturases (ω-3 FADs). The quality of peanut oil would be much improved if the content of ALA could be increased. A scan of the peanut genome revealed that it harbored 36 FAD genes, mapping to 16 of the species’ 20 chromosomes. A phylogenetic analysis concluded that these genes belonged to six sub-families, namely stearoyl-acyl-acyl carrier protein desaturases ( SAD ), FAD2 , FAD3 , FAD4/5 , FAD6 and FAD7/8 . Of these, FAD3 and FAD7/8 encoded ω-3 FADs, while genes belonging to the other four sub-families encoded ω-6 FADs. Based on RNA-Seq data, each of the 36 FAD genes was shown to be transcribed in non-stressed plants, but there was variation between them with respect to which organs they were transcribed in. Four ω-3 AhFAD3 genes were functionally characterized; when expressed in Arabidopsis thaliana protoplasts, each was localized mainly in the endoplasmic reticulum, while within peanut, the genes were more strongly transcribed in the developing seed than in either the root or the leaf. When constitutively expressed in Arabidopsis thaliana , both the total fatty acid content of the seed and the relative contribution of ALA were increased. The transgenic seedlings also exhibited an improved level of survival when challenged by salinity stress.

Divergence of Iodine and Thyroid Hormones in the Fetal and Maternal Parts of Human-Term Placenta - Shiqiao Peng; Chenyan Li; Xiaochen Xie; Xiaomei Zhang; Danyang Wang; Xixuan Lu; Manni Sun; Tao Meng; Shiwei Wang; Yaqiu Jiang; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

Relative roles of formation and preservation on gold endowment along the Sanshandao gold belt in the Jiaodong gold province, China: importance for province- to district-scale gold exploration - Liang Zhang; David I. Groves; Li-Qiang Yang; Gong-Wen Wang; Xiang-Dong Liu; Da-Peng Li; Ying-Xin Song; Wei Shan; Si-Chen Sun; Zhao-Kun Wang (Mineralium Deposita, 2020)

Asperfurandiones A and B, two antifungal furandione analogs from a marine-derived fungus Aspergillus versicolor - Lijian Ding; Peng Xu; Te Li; Xiaojian Liao; Shan He; Shihai Xu (Natural Product Research, 2019)

Fluorophenols bearing nitrogenated heterocycle moieties, a class of novel Keap1-Nrf2 protein-protein interaction inhibitors: synthesis, antioxidant stress screening and molecular docking - Xiu E Feng; De Peng Kong; Shu Rong Ban; Rui Ge; Qing Shan Li (Medicinal Chemistry Research, 2019)

Initial Soil Organic Matter Content Influences the Storage and Turnover of Litter, Root and Soil Carbon in Grasslands - Shan Xu; Ping Li; Emma J. Sayer; Beibei Zhang; Jing Wang; Chunlian Qiao; Ziyang Peng; Liwei Diao; Yonggang Chi; Weixing Liu; Lingli Liu (Ecosystems, 2018)

Hydrological response of biological soil crusts to global warming: A ten‐year simulative study - Xin‐Rong Li; Rong‐Liang Jia; Zhi‐Shan Zhang; Peng Zhang; Rong Hui (Global Change Biology, 2018)
Biological soil crusts across the desert regions play a key role in regional ecological security and ecological health. They are vital biotic components of desert ecosystems that maintain soil stability, fix carbon and nitrogen, influence the establishment of vascular plants, and serve as habitats for a large number of arthropods and microorganisms, as well as influencing soil hydrological processes. Changes in temperature and precipitation are expected to influence the functioning of desert ecosystems by altering biotic components such as the species composition of biological soil crusts. However, it remains unclear how these important components will respond to the prolonged warming and reduced precipitation that is predicted to occur with climate change. To evaluate how the hydrological properties of these biological soil crusts respond to these alterations, we used open‐top chambers over a 10‐year period to simulate warming and reduced precipitation. Infiltration, dew entrapment, and evaporation were measured as surrogates of the hydrological functioning of biological soil crusts. It was found that the ongoing warming coupled with reduced precipitation will more strongly affect moss in crustal communities than lichens and cyanobacteria, which will lead to a direct alteration of the hydrological performance of biological soil crusts. Reductions in moss abundance, surface cover, and biomass resulted in a change in structure and function of crustal communities, decreased dew entrapment, and increased infiltration and evaporation of biological soil crusts in desert ecosystems, which further impacted on the desert soil water balance.

Rapid estimation of microbial biomass in acid red soils with and without substrate incorporation - Peng Su; Yong Liu; Sifan Wang; Zhongqi Yan; Shan Wang; Lian Zhu; Jun Lou; Fangbai Li (Journal of Soils and Sediments, 2018)

Phagocytosis Deficiency of Macrophages in NOD.H-2h4 Mice Accelerates the Severity of Iodine-Induced Autoimmune Thyroiditis - Xue He; Chuhui Xiong; Aihua Liu; Wei Zhao; Xinghai Xia; Shiqiao Peng; Chenyan Li; Mi Zhou; Yushu Li; Xiaoguang Shi; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2018)

Effects of autophagy on acid-sensing ion channel 1a-mediated apoptosis in rat articular chondrocytes - Ya-Ya Xie; Yue Li; Ren-peng Zhou; Bei-Bei Dai; Yue-jiao Qian; Xiao-shan Wu; Jin-fang Ge; Wei Hu; Fei-hu Chen (Molecular and Cellular Biochemistry, 2018)

Cloning, purification and biochemical characterisation of a GH35 beta-1,3/beta-1,6-galactosidase from the mucin-degrading gut bacterium Akkermansia muciniphila - Bi-Shan Guo; Feng Zheng; Lucy Crouch; Zhi-Peng Cai; Meng Wang; David N. Bolam; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2018)

A nowcasting model for the prediction of typhoon tracks based on a long short term memory neural network - Song Gao; Peng Zhao; Bin Pan; Yaru Li; Min Zhou; Jiangling Xu; Shan Zhong; Zhenwei Shi (Acta Oceanologica Sinica, 2018)

Effect of Iodine Nutrition on Pregnancy Outcomes in an Iodine-Sufficient Area in China - Yue Xiao; Huakun Sun; Chenyan Li; Yongze Li; Shiqiao Peng; Chenling Fan; Weiping Teng; Zhongyan Shan (Biological Trace Element Research, 2018)

Estimation of Human Norovirus Infectivity from Environmental Water Samples by In Situ Capture RT-qPCR Method - Peng Tian; David Yang; Lei Shan; Qianqian Li; Danlei Liu; Dapeng Wang (Food and Environmental Virology, 2018)

Inhibitory neurotransmitter serotonin and excitatory neurotransmitter dopamine both decrease food intake in Chinese perch (Siniperca chuatsi) - Yu-Hui He; Ling Li; Xu-Fang Liang; Shan He; Luo Zhao; Yan-Peng Zhang (Fish Physiology and Biochemistry, 2018)

Complementary feeding patterns among ethnic groups in rural western China - Peng-fei Qu; Ya Zhang; Jia-mei Li; Ruo Zhang; Jiao-mei Yang; Fang-liang Lei; Shan-shan Li; Dan-meng Liu; Shao-nong Dang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2018)

Effects of vermicompost amendment as a basal fertilizer on soil properties and cucumber yield and quality under continuous cropping conditions in a greenhouse - Hai-Tao Zhao; Tian-Peng Li; Yang Zhang; Jian Hu; Yan-Chao Bai; Yu-Hua Shan; Feng Ke (Journal of Soils and Sediments, 2017)

Design, synthesis and cytotoxic evaluation of a novel series of benzo[d]thiazole-2-carboxamide derivatives as potential EGFR inhibitors - Lan Zhang; Xin-Shan Deng; Chao Zhang; Guang-Peng Meng; Jiao-Feng Wu; Xue-Song Li; Qing-Chun Zhao; Chun Hu (Medicinal Chemistry Research, 2017)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Effects of resource addition on recovery of production and plant functional composition in degraded semiarid grasslands - Qing Chen; David U. Hooper; Hui Li; Xiao Ying Gong; Fei Peng; Hong Wang; Klaus Dittert; Shan Lin (Oecologia, 2017)

ApoA-I/SR-BI modulates S1P/S1PR2-mediated inflammation through the PI3K/Akt signaling pathway in HUVECs - Kun Ren; Yan-Ju Lu; Zhong-Cheng Mo; Xing -Liu; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Li Li; Qing-Hai Zhang; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2017)

Impacts of meteorological and environmental factors on allergic rhinitis in children - Shan He; Zhe Mou; Li Peng; Jie Chen (International Journal of Biometeorology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

MCP1 triggers monocyte dysfunctions during abnormal osteogenic differentiation of mesenchymal stem cells in ankylosing spondylitis - Zhongyu Xie; Peng Wang; Jinteng Li; Yuxi Li; Shan Wang; Xiaohua Wu; Suhe Sun; Shuizhong Cen; Hongjun Su; Wen Deng; Zhenhua Liu; Yi Ouyang; et al. (Journal of Molecular Medicine, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

A new flavone C -glycoside and a new bibenzyl from Bulbophyllum retusiusculum - Ming-Hui Yang; Yun-Shan Fang; Le Cai; Ying Li; Jian-Wei Dong; Tian-Peng Yin; Cai-Li Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Two new abietane diterpenoid glycosides from Clinopodium chinense - Yin-Di Zhu; Jing-Yi Zhang; Peng-Fei Li; Hai-Feng Wu; Nai-Liang Zhu; Hai Jiang; Cui-Yan Lv; Li-Li Wu; Ze-Xin Ma; Xu-Dong Xu; Guo-Xu Ma; Jun-Shan Yang (Natural Product Research, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

NCoR negatively regulates adipogenic differentiation of mesenchymal stem cells - Gao Hong-Wei; Liu Lan; Xing De-Guo; Liu Zhong-Hao; Ren Peng; Li Zhi-Qiang; Shan Guo-Qiang; Gong Ming-Zhi (In Vitro Cellular & Developmental Biology - Animal, 2015)

I nner M ongolian steppe arbuscular mycorrhizal fungal communities respond more strongly to water availability than to nitrogen fertilization - Xiaoliang Li; Tingyao Zhu; Fei Peng; Qing Chen; Shan Lin; Peter Christie; Junling Zhang (Environmental Microbiology, 2015)
Summary Plant community productivity and species composition are primarily constrained by water followed by nitrogen ( N ) availability in the degraded semi‐arid grasslands of I nner M ongolia. However, there is a lack of knowledge on how long‐term N addition and water availability interact to influence the community structure of arbuscular mycorrhizal ( AM ) fungi, and whether AM fungi contribute to the recovery of degraded grasslands. Soils and roots of the dominant plant species S tipa grandis and A gropyron cristatum were sampled under two water levels and N ) rates after 8 years. The abundance and diversity of AM fungi remained relatively resilient after the long‐term addition of water and N . Variation in the AM fungal communities in soils and roots were affected primarily by watering. AM fungal abundance and operational taxonomic unit ( OTU ) richness were significantly correlated with average aboveground net primary productivity and biomass of plant functional groups. Hyphal length density was significantly correlated with plant richness, the average biomass of S . grandis and perennial forbs. Both water and plant biomass had a considerable influence on the AM fungal assemblages. The tight linkages between AM fungi with aboveground plant productivity highlight the importance of plant–microbe interactions in the productivity and sustainability of these semi‐arid grassland ecosystems.

Simultaneous quantification of 10 saponins in Chinese Shizhu Panax by UPLC-ESI-MS - Qi Jiang; Long-Shan Zhao; Zhi-Li Xiong; Xu-Ling Peng; Xing-Jie Guo (Natural Product Research, 2015)

Isolation and molecular characterization of an ethylene response factor NtERF1-1 in Nicotiana tabacum cv. Xanthi - Jun-Shan Gao; Li Hu; Peng Xie; Yan Meng; Yong-Ping Cai; Yi Lin (Journal of Biosciences, 2014)

Anti-apoptosis effect of polysaccharide isolated from the seeds of Cuscuta chinensis Lam on cardiomyocytes in aging rats - Shou-Li Sun; Li Guo; Ya-Chao Ren; Bing Wang; Rong-Hui Li; Yu-Shan Qi; Hui Yu; Nai-Dan Chang; Ming-Hui Li; Hai-Sheng Peng (Molecular Biology Reports, 2014)

Coffee consumption and prostate cancer risk: an updated meta-analysis - Yu Lu; Limin Zhai; Jie Zeng; Qiliu Peng; Jian Wang; Yan Deng; Li Xie; Cuiju Mo; Shi Yang; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

Modulation of Lipid Metabolism by Deep-Sea Water in Cultured Human Liver (HepG2) Cells - Shan He; Jiejie Hao; Weibing Peng; Peiju Qiu; Chunxia Li; Huashi Guan (Marine Biotechnology, 2014)

Association between statin use and colorectal cancer risk: a meta-analysis of 42 studies - Yanqiong Liu; Weizhong Tang; Jian Wang; Li Xie; Taijie Li; Yu He; Yan Deng; Qiliu Peng; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Tumour necrosis factor alpha (TNF-α) genetic polymorphisms and the risk of autoimmune liver disease: a meta-analysis - SHAN LI; XIAMEI HUANG; HUIZHI ZHONG; ZHIPING CHEN; QILIU PENG; YAN DENG; XUE QIN (Journal of Genetics, 2013)

Genes encoding the production of extracellular polysaccharide bioflocculant are clustered on a 30-kb DNA segment in Bacillus licheniformis - Shan Yan; Na Wang; Zhen Chen; Yuanpeng Wang; Ning He; Yajuan Peng; Qingbiao Li; Xu Deng (Functional & Integrative Genomics, 2013)

Association between non-steroidal anti-inflammatory drug use and melanoma risk: a meta-analysis of 13 studies - Shan Li; Yanqiong Liu; Zhiyu Zeng; Qiliu Peng; Ruolin Li; Li Xie; Xue Qin; Jinmin Zhao (Cancer Causes & Control, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Development of a polyprobe for the simultaneous detection of four grapevine viroids in grapevine plants - Zhixiang Zhang; Shan Peng; Dongmei Jiang; Song Pan; Hongqing Wang; Shifang Li (European Journal of Plant Pathology, 2012)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Movement patterns of Bar-headed Geese Anser indicus during breeding and post-breeding periods at Qinghai Lake, China - Peng Cui; Yuansheng Hou; Mingjie Tang; Haiting Zhang; Yuanchun Zhou; Zuohua Yin; Tianxian Li; Shan Guo; Zhi Xing; Yubang He; Diann J. Prosser; Scott H. Newman; et al. (Journal of Ornithology, 2011)

A novel wall-associated receptor-like protein kinase gene, OsWAK1, plays important roles in rice blast disease resistance - Hui Li; Shan-Yue Zhou; Wen-Sheng Zhao; Sheng-Chang Su; You-Liang Peng (Plant Molecular Biology, 2009)

Genetic diversity and phylogenetic analysis of Australian Grapevine Viroid (AGVd) isolated from different grapevines in China - Dongmei Jiang; Shan Peng; Zujian Wu; Zhuomin Cheng; Shifang Li (Virus Genes, 2009)

Triptolide protects against 1-methyl-4-phenyl pyridinium-induced dopaminergic neurotoxicity in rats: Implication for immunosuppressive therapy in Parkinson’s disease - Jun-Peng Gao; Shan Sun; Wen-Wei Li; Yi-Ping Chen; Ding-Fang Cai (Neuroscience Bulletin, 2008)

Lake-Level Change and Water Balance Analysis at Lake Qinghai, West China during Recent Decades - Xiao-Yan Li; He-Ye Xu; Yong-Liang Sun; Deng-Shan Zhang; Zhi-Peng Yang (Water Resources Management, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)

A study on equilibrium coastal profiles of the close tidal flat - Heng-peng Li; Gui-shan Yang (Chinese Geographical Science, 2002)

Identification of an 85-kb DNA fragment containing pms1, a locus for photoperiod-sensitive genic male sterility in rice - N. Liu; Y. Shan; F. Wang; C. Xu; K. Peng; X. Li; Qifa Zhang (Molecular Genetics and Genomics, 2001)